The effects of carcass conditioning on shear force values and water holding capacity of different skeletal muscles of Malaysian indigenous (MALIN) sheep and the changes in their pH and glycogen contents. - Sazili, Awis Qurni; Abdullah, Mohamad Hilmi; Olusesan, Akanbi Taiwo; Panandam, Jothi Malar (Medwell Online, 2011)
This study investigated the effects of carcass conditioning on shear force values and water holding capacity of various major skeletal muscles (Infraspinatus, Supraspinatus, Triceps brachii, Longissimus dorsi, Rectus femoris, Vastus lateralis, Semitendinosus, Semimembranosus and Adductor femoris) obtained from a total of 18, 1 year old Malaysian Indigenous rams. It also studied the effect of conditioning on changes in their pH and glycogen contents. Sequel to the conditioning, muscle samples were analysed for shear force values and water holding capacity. The postmortem conditioning resulted in significant decline (p>0.05) in muscle pH, glycogen, shear force values and drip loss while the cooking loss remained unaffected. Statistically, there was no interaction (p>0.05) between the conditioning period and muscle type and this indicates that the effects of conditioning on muscle pH, shear force values, drip loss and cooking loss were independent of the muscle type. Meanwhile, its effect on glycogen was influenced by the muscle type.